PSYCHOLOGICAL PREPARATION OF STUDENT YOUTH FOR COMPETITIVE ACTIVITIES - M. M. Azizov,; A. K. Shamshetova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the psychological preparation of student youth for participation in competitive sports activities. It examines the interplay between psychological readiness, emotional resilience, and motivational factors in shaping competitive performance. The study emphasizes the importance of psychological training as a critical determinant of students’ success, highlighting that targeted preparation can account for 30–40% of competition outcomes. By drawing on national policy priorities, empirical observations, and pedagogical-psychological perspectives, the article argues that developing students’ self-regulation, emotional stability, and motivational endurance is as crucial as physical training. Finally, it proposes practical recommendations for integrating psychological training into the broader system of sports education and competitions.